this equation can be written as (D4-2D3+2D2)y = (3+2x)e-x+sinx.e-x ....(1)
the auxiliary equation is
D4-2D3+2D2=0
D= 0,0,1+i,1-i
so, the complimenatry function is
y= c1+c2x + ex(c3 cosx + c4sinx)
let trial solution be
z= e-x(A sinx + B cosx) + e-x(D+Ex)
Dz= -e-x( A sinx + B cosx + D+Ex) + e-x( A cosx - B sinx + E )
D2z= e-x( D+Ex) -2e-x(A cosx - B sinx +E)
D3z = -e-x(-2A sinx -2B cosx + D+Ex) + 3e-x(A cosx - B sinx +E)
D4z = e-x( -5A sinx -5 B cosx + D+Ex) - e-x(A cosx - B sinx + 4E )
putting these values in (1), we get
e-x[ sinx(-9A+9B) + x (5E) + 5D -14E + cosx(-9B-9A)] = e-x(3+2x+ sinx)
comparing coefficients
A=-1/18
B=1/18
D=43/25
E= 2/5
So, the solution is
y= c1+(c2+0.4e-x)x + ex(c3 cosx + c4sinx) + e-x[( -1/18) . sinx + (1/18) . cosx + (43/25 )]
Comments
Leave a comment